Integration of Local Etiquette in Building Students’ Psychological Resilience and Suicide Prevention in the Talaud Islands Regency - Jane Elvira Scipio; Gretha Paduli; Lalira, James; Yopie A.T. Pagemananan; Barrylyn S. H. Kussoy; Morshe E. Lumansik; Erens Sanggelorang; Jola Silvana Kalangi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aimed to examine the potential of integrating local etiquette values into the education system as a strategy to enhance students’ psychological resilience and prevent suicide, particularly in remote regions such as the Talaud Islands Regency. With rising suicide rates and limited access to professional mental health services, there is a pressing need for alternative, culturally grounded, and contextually relevant approaches. A mixed-methods research design was employed, combining qualitative analysis through in-depth interviews, focus group discussions, and participatory observation involving teachers, students, parents, and community leaders in Gemeh District, along with quantitative analysis using culturally adapted instruments including resilience scales and psychological assessments. The findings indicate that local etiquette values, such as respect for privacy, social responsibility, and interpersonal boundaries, play a significant role in fostering a supportive environment and reducing psychosocial stress, especially for students with intellectual limitations. The internalization of these values has been shown to enhance feelings of safety, social acceptance, and self-regulation, which are key components in building psychological resilience. Based on these results, it is recommended that local etiquette values be systematically incorporated into local content curricula and school counseling programs. Training teachers and counselors in culture-based inclusive education, collaborating with traditional leaders, and dedicated budget allocation by local authorities are essential for ensuring the sustainability of such interventions. This approach holds promise as a community-based mental health model that can be adapted and replicated in other island regions that face similar challenges.